KEWAJIBAN PAJAK PENGHASILAN UMKM WAJIB PAJAK ORANG PRIBADI (STUDI KASUS PADA TOKO CSG) - Mozart, Mohammad; Fatimah, Hayati; Purwaji, Agus (Jurnal Akuntansi Keuangan dan Perbankan, 2018)
ABSTRACT The main source of income for a major State is comes from tax revenues. The imposition of income tax, especiallyin the MSME?s sector (Micro, Small Medium Enterprises) has a huge potential revenue, but the awareness ofTaxpayers to comply with it?s obligations is still low. Therefore, the government attempts to issue tax rules inorder to facilitate the perpetrators of MSME?s with the method of recording to pay the Final Income Tax of 1%of the business turnover per month. Along with the rises development of UMKM business with a turnover aboveRp 4.800.000.000 are required to do bookkeeping in accordance with applicable provisions although very simple.But not all business owners are able to do bookkeeping because of the limitations of resources by the owner. Thepurpose of this research is to assist the MSME?s required by the rules to conduct bookkeeping in applyingobligations as Taxpayer in accordance with the provisions of the Tax Law. This type of qualitative research is acase study. The method of data collection obtained through literature study, interview, observation, anddocumentation. Data analysis techniques use data reduction, data presentation, and verification. The result ofthis research shows that the obligation of taxation required on CSG trade store 2017 is not fully done consideringthe incapability of the resources by the owner to do bookkeeping and pay the installment of Income Tax Article25.  Keywords: Income Tax (PPh), MSME?s, Recording, Bookkeeping ABSTRAK Sumber utama penerimaan suatu Negara terbesar berasal dari penerimaan pajak. Penerimaan Pajak Penghasilan(PPh) khususnya pada sektor UMKM memiliki potensi penerimaan yang sangat besar, namun kesadaran WajibPajak (WP) untuk mematuhi kewajibannya masih tergolong rendah. Oleh karena itu, pemerintah berupayamenerbitkan aturan pajak dengan tujuan untuk memudahkan para pelaku UMKM dengan metode pencatatanuntuk membayar PPh Final 1% dari omset usaha perbulan. Seiring perkembangan bisnis yang semakin cepatUMKM dengan omset diatas Rp. 4.800.000.000,- dituntut untuk melakukan pembukuan sesuai ketentuan yangberlaku walaupun dengan sangat sederhana. Tujuan dari penelitian ini adalah membantu UMKM dalam memenuhikewajiban sebagai WP sesuai Ketentuan Undang-Undang Perpajakan. Jenis penelitian kualitatif yang digunakanadalah studi kasus. Teknik Pengumpulan Data yang digunakan berupa studi kepustakaan, wawancara, observasidan dokumentasi. Teknik Analisis yang digunakan berupa teknik analisis reduksi data, penyajian data danverifikasi. Hasil penelitian menunjukan bahwa kewajiban perpajakan yang diwajibkan pada UMKM Toko CSGtahun 2017 yaitu melakukan pembukuan dan membayar angsuran PPh Pasal 25, hal tersebut belum sepenuhnyadilakukan mengingat terbatasnya sumber daya yang dimiliki. Kata Kunci: Pajak Penghasilan (PPh), UMKM, Pencatatan, Pembukuan